Model Rekam Jejak Ritual Ngabubur dalam Film Dokumenter - Yanti Heriyawati; Enok Wartika; Apip - (LP2M ISBI Bandung, 2013)
ABSTRACT This study describes how the ngabubur ritual is represented into a documentary film. The factual data of Ngabubur ritual is collected through ethnographic methods. In terms of methods, the film was made through some stages: designing, researching, shooting, editing and finishing. Ngabubur is an annual ritual of Rancakalong society as a form of Sukur Bumi, an act of gratitude from agricultural products that have been enjoyed by the community. The Film narrative is based on the actual event structures. The meaning given to the film is greatly influenced by the propriety and authenticity of its images. Keywords: documenter film, ngabubur, etnografi, and narrative ABSTRAK Ritual ngabubur direpresentasi ke dalam bentuk film dokumenter. Data faktual ritual ngabubur dikumpulkan melalui metode etnografi. Secara metodis film dibuat melalui tahap perumusan design, research, shooting, editing, dan finishing. Ngabubur merupakan ritual tahun- an masyarakat Rancakalong sebagai bentuk sukur bumi, wujud syukur dari hasil bumi yang telah dinikmati oleh masyarakat. Naratif film dibuat berdasarkan struktur peristiwanya. Pemaknaan filmnya sangat dipengaruhi oleh kebenaran citra dan keotentikan dalam pe- nyajiannya. Kata kunci: film dokumenter, ngabubur, etnografi, dan naratif